GAMBARAN CT-SCAN NEOPLASMA INTRAKRANIAL DI BAGIAN / SMF RADIOLOGI FK UNSRAT RSUP PROF. DR. R. D. KANDOU MANADO PERIODE OKTOBER 2014 - SEPTEMBER 2015 - Dewi, Maharani; Loho, Elvie; Tubagus, Vonny N. (e-CliniC, 2016)
Abstract: Brain is a vital organ that plays very important roles for the body. One of  diseases that attacks the brain is brain tumor. A radiology modality, the CT scan, is very valuable for diagnosis and evaluation the suspected brain tumor. It can be used to evaluate the difference between tumor tissue and others, especially by using contrast agents. This study aimed to identify the CT Scan imaging of patients with intracranial neoplasms. This was a descriptive retrospective study. Data were obtained  from the request form sheets and radiographic results of brain CT-Scan in the Department of Radiology Prof. Dr. R. D. Kandou Hospital Manado. Samples were patients that were radiologically diagnosed as primary brain tumor. The results showed that of the 171 data of SOL intracranial patients, 59 patients (34.5%) had been radiologically diagnosed as intracranial neoplasms. There were more females (62.7%) than males (37.3%). The age group, 36-45 years was the largest with 15 patients (25.4%). The area of most lesions was parietal lobe with 16 cases (27.1%). The most frequent diagnosis was meningioma (45.8%). Keywords: intracranial neoplasm, CT scan Abstrak: Otak merupakan organ vital yang berperan sangat penting bagi tubuh. Salah satu penyakit yang banyak menyerang otak ialah tumor otak. Modalitas radiologi yang penting dalam evaluasi pasien yang diduga tumor otak ialah CT-Scan. Dengan menggunakan CT-Scan dapat terlihat perbedaan antara jaringan tumor yang satu dengan yang lain, dan dapat diperjelas dengan penggunaan zat kontras. Penelitian ini bertujuan untuk mengetahui gambaran CT-Scan penderita neoplasma intrakranial. Jenis penelitian deskriptif retrospektif. Data diambil dari lembaran permintaan dan jawaban CT-Scan otak di Bagian Radiologi RSUP Prof. Dr. R. D. Kandou Manado. Sampel yang diambil ialah pasien dengan gambaran radiologi tumor intrakranial primer. Berdasarkan 171 data pasien SOL intrakranial yang didapat, 59 pasien dengan diagnosis radiologis neoplasma intrakranial; lebih banyak perempuan (62,7%) dibandingkan laki-laki (37,3%). Berdasarkan kelompok umur, didapatkan  paling banyak pada kelompok umur 36-45 tahun (25,4%). Lokasi paling banyak ditemukan lesi ialah lobus parietalis (27,1%). Jenis tumor intrakranial terbanyak ialah meningioma (45,8%).Kata kunci: neoplasma intrakranial, computed tomography scan